Membangun Keadilan Kewarganegaraan melalui Sinergi Nilai Islam dan Pancasila - Ammelia Anna Vhony; Sidiatafa Nur Fauziah; Annisa Nurhanifah; Alifah Nur Anisah (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study addresses citizenship justice in Indonesia amid the challenging era of globalization, focusing on the conflict between Pancasila as the state foundation and the dominant Islamic values in society. The study aims to analyze the synergy of Islamic principles—justice (ʿadl), equality (musawah), and public welfare (maslahah)—with the second and fifth principles of Pancasila to build sustainable and inclusive citizenship justice. The method used is qualitative, including content analysis and an in-depth literature review of the Qur'an, Hadith, and Pancasila documents, supplemented by semi-structured interviews with 20 experts in religion and constitutional law. The findings reveal a new conceptual framework called "Islamic Pancasila," which integrates the principle of tauhid with the value of gotong royong (mutual cooperation), reducing social polarization by up to 30% based on case simulations in multicultural areas like West Java. Islamic values provide a spiritual dimension that complements Pancasila, while Pancasila offers an inclusive nationalist framework. The study concludes that the synergy between Islamic values and Pancasila is not only a theoretical solution but also a practical strategy for realizing citizenship justice. Recommendations include integrating these values into the civic education curriculum and government policies to facilitate interfaith dialogue, strengthening national identity amid contemporary social and cultural dynamics.